A ecological study of galamsey activities in Ghana and their physiological toxicity - Ofori, Samuel Ayetibo; Dwomoh, Joshua; Yeboah, Enoch Owusu; Aggrey, Martin Leo; Nti, Samuel; Philip, Amankwah; Asante, Clement (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Small-Scale Small-Scale Gold Mining (ASGM), locally known as